Nutritional and physico-chemical properties of selected oyster sauce products. - Nacional, Loda M. (Miagao, Iloilo College of Fisheries, University of the Philippines in the Visayas, 2000)
Nutritive values of oyster sauce products were determined. Proximate composition, mineral (calcium, iron, phosphorus and iodine), and cholesterol contents were analysed. Phisico chemical properties of the products were likewise evaluated based on sensorial attributes. Oyster sauce such as the gold cup, yuen yick, nguan chiang as well as the freshly produced sample gave a variable nutritional composition. Moisture contents of the commercial samples ranged from 59-67% whilst protein ranged from 5.4 to 10.8%. lipid, ash and carbohydrate contents ranged from 0.1-0.2%, 8.2-12.4% and 9.1-13.0% respectively. The freshly-produced oyster sample had a 68% moisture content i.e., 24 to 15.4% higher than those of the commercial samples and a protein content which was about 41% lower than those of the latter. Lipid, ash and carbohydrate contents were closely similar to those of the commercial samples. Both commercial and freshly produced samples were fiber-free. Mineral contents of all samples were insignificant (less tha 1% of the body's daily requirement) except for the iron content of gold cup, yuen yick and the freshly produced oyster sauce sample, which had met 2.8-5.5% of the Philippine RDA value. Both the commercial and freshly produced oyster sauce had low fat(~,0.4) and low cholesterol (~,2..5 mg) contents hence, could be considered as heart-healthy foods. Gold cup had the thickest consistency of the three commercial samples evaluated i.e., 0.049 centipoise, which about 29% lower than that of the gold cup. All these products gave a pH values between 4.76 and 5.51 and salt contents of 6.53 to9.01%, making them theoretically stable. Panellists preferred the sample (gold cup) that was slightly brown in color; with combined sweet and salty taste; with slightly discernable oyster flavour; and with medium thick consistency.
Thesis
Keywords: Oyster -- Sauce profucts